2006
DOI: 10.1016/j.virol.2006.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement for CD28 and CD80/86 pathways of costimulation in the long-term control of murine gammaherpesvirus-68

Abstract: The costimulatory molecules CD80 and CD86 (B7-1 and B7-2) are upregulated on mature antigen-presenting cells and interact with positive and negative regulators of CD8 T cell function, CD28 and CD152 (CTLA4) respectively. In this study, we examined the role of CD80 and CD86 in the immune response to murine gammaherpesvirus-68 (MHV-68) using CD80/86-/- mice. As we had previously shown that CD28 (the only known activating receptor for CD80 and 86) is not essential for long-term control of MHV-68, we predicted tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
(50 reference statements)
2
29
0
Order By: Relevance
“…Consequently, these results indicate that the absence of B7.1/B7.2 has a more profound impact on the LCMV-specific immune response than does the lack of CD28, and the results may therefore suggest that there are additional stimulatory receptors for B7.1/B7.2 besides CD28. A few other studies have pointed toward the same conclusion (19)(20)(21), but so far no such receptor has been unequivocally identified.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consequently, these results indicate that the absence of B7.1/B7.2 has a more profound impact on the LCMV-specific immune response than does the lack of CD28, and the results may therefore suggest that there are additional stimulatory receptors for B7.1/B7.2 besides CD28. A few other studies have pointed toward the same conclusion (19)(20)(21), but so far no such receptor has been unequivocally identified.…”
Section: Discussionmentioning
confidence: 86%
“…In view of the fact that these issues had not been optimally dealt with in earlier studies on LCMV infection, we considered it important to revisit the role of CD28-B7 in inducing and maintaining LCMV-specific CD8 T cell memory, with the reason being that it would be very important to know if certain viruses would have the capacity to induce not only initial T cell activation, but also completely normal memory differentiation in the absence of this key costimulatory interaction. Our interest was further fueled by a few recent reports suggesting that there might be other stimulatory receptors for B7 than CD28 (19)(20)(21) and that earlier studies of the LCMV infection might have failed in finding a key role for B7 costimulation, because these studies had been performed in CD28 mice have no obvious phenotype following infection with MHV68, T cell-dependent immune surveillance eventually completely collapses in MHC class II-deficient mice, and, interestingly, analysis of B7.1/B7.2 2/2 mice revealed that these mice lay between these two extremes. This is similar to the situation in mice infected with moderate doses of rapidly invasive strains of LCMV, where the infection is efficiently controlled in CD28-deficient mice (17) but leads to late recrudescence of viremia and severe disease in MHC class II-deficient mice (22).…”
mentioning
confidence: 99%
“…The CD40L-CD40 pathway is essential for long-term immunological control of latent infection (44,45). The CD80/CD86-CD28 pathway has a significant impact in the antiviral humoral (42,46), and cellular (46,47) responses, and low levels of viral reactivation during latency is observed in the lungs of CD80/CD86 Ϫ/Ϫ mice (47,48). In this study, we investigated the role of the 4-1BBL-4-1BB pathway in immune surveillance of MHV-68 infection.…”
Section: Ostimulatory Signals Provide Secondary Signals To T Cells mentioning
confidence: 99%
“…For example, paralysis following local HSV-1 infection was aggravated by CTLA-4Ig-mediated CD80/86 blockade but not in CD28 Ϫ/Ϫ mice (20). Similarly, viral reactivation occurred in the lungs of MHV-68-infected CD80/86 Ϫ/Ϫ but not CD28 Ϫ/Ϫ (22,42,54), anti-CTLA-4-treated CD28 Ϫ/Ϫ (22), or CD28 Ϫ/Ϫ /CTLA-4 Ϫ/Ϫ mice (18), leading to the postulate of an unidentified (activating) receptor for CD80/86, a notion that has also been advanced in models of cardiac allograft transplantation (55,82). Most recently, primary MCMV-specific CD8 ϩ T E responses were shown to be somewhat more compromised in CD80/86 Ϫ/Ϫ or anti-CD80/86 antibody-treated wt mice than in CD28 Ϫ/Ϫ mice (3), and exacerbated phenotypic alterations and functional defects of CD8 ϩ T M populations combined with impaired virus control in CD80/86 Ϫ/Ϫ but not CD28 Ϫ/Ϫ mice infected with the more virulent LCMV Traub strain have prompted similar speculations about additional CD80/86 receptors (28).…”
mentioning
confidence: 98%
“…To date, infections with multiple distinct and related viruses, escalating dosages, and various challenge routes have been employed to ascertain the role of CD28-CD80/86 costimulation preferentially in CD28 Ϫ/Ϫ mice but also complemented by analyses of CD80 Ϫ/Ϫ and/or CD86 Ϫ/Ϫ strains as well as ligand (anti-CD80/86 and CTLA-4Ig) and receptor (anti-CD28 and anti-CTLA-4) blockade. These viruses include LCMV (1,15,25,28,36,44,45,65,69,72,73,81); vesicular stomatitis virus (VSV) (1, 15, 43-45, 58, 69); vaccinia virus (VACV) (21,23,24,45,67,70) and the related ectromelia virus (ECTV) (21); influenza A virus (5,7,8,10,14,29,32,51,53,74), herpes simplex viruses (herpes simplex virus 1 [HSV-1] and HSV-2) (10,20,75,76); murine gammaherpesvirus 68 (MHV-68) (18,22,24,42,47,54); polyomavirus (PyV) (41), murine cytomegalovirus (MCMV) (2,3,17); and adenovirus …”
mentioning
confidence: 99%